Malignant Melanoma Arising From a Giant Congenital Melanocytic Nevus in a 3-Year Old: Review of Diagnosis and Management. Issue 4 (9th June 2021) - Kugar, Meredith; Akhavan, Arya; Ndem, Idorenyin; Ollila, David; Googe, Paul; Blatt, Julie; Wood, Jeyhan
Abstract : Introduction: Giant congenital nevi (GCN), defined as abnormal collections of melanocytes with a diameter greater than 20 cm, occur in 1 in 20, 000 births. The lifetime risk of malignant transformation in GCN is reported between 5% and 20% and most commonly occurs in the first 3 to 5 years of life. This article reviews the risk factors of malignant transformation and highlights the diagnostic challenges of malignant melanoma in the pediatric population utilizing a clinical report of a patient with GCN. Case Description: A male patient with giant congenital nevus of the scalp with over 20 satellite nevi was evaluated at the authors' institution at 1 week of life. Beginning at 9 months of age, he underwent serial excision of GCN and satellite lesions. Initial pathology showed compound congenital melanocytic nevus. Subsequent pathology on serial excisions demonstrated compound nevus with clonal expansion of pigmented epithelioid melanocytoma (PEM). He then underwent complete excision of GCN. Pathology demonstrated malignant melanoma that was confirmed by consensus review with outside institutions. The patient was diagnosed with stage III metastatic melanoma after further imaging. He was treated with cervical nodal dissection and interferon alpha-2b. At the time of last visit, the patient had no evidence of melanoma. Discussion: This case highlights the difficulties of clinical and pathologic diagnosis of malignant melanoma in the setting of GCN. Pathology can vary between biopsy sites and initial biopsies can suggest nonmalignant melanocytic lesions, as demonstrated in this patient's case. Correct histologic evaluation often requires input from a relatively few centers that treat a larger volume of childhood melanoma. Analysis of gene expression profiles aids in accurate diagnosis of PEM, proliferative nodule or melanoma. It is important to differentiate PEM, a low-grade, indolent melanoma, from malignant melanoma as the treatment differs significantly. Review of pathology by expert dermatopathologists from multiple institutions is vital for diagnostic accuracy, and patients with malignant transformation of GCN are best served by multidisciplinary teams.